2003
DOI: 10.1002/mds.10704
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographically‐controlled injection of botulinum toxin into the longus colli muscle in severe anterocollis

Abstract: We report on a 44-year-old man who suffered from severe anterocollis. Repeated computed tomographically controlled injections of botulinum toxin into the right longus colli muscle allowed a precise location of the needle and injection of the toxin, leading to clear improvement of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 14 publications
(11 reference statements)
0
21
0
Order By: Relevance
“…Because of the weak effect he did not return to treatment earlier than after 2 years when he received 35 MU of onaBTXA into each sternocleidomastoid muscle and 30 MU onaBTXA into the right longus colli muscle under CT-guidance [39]. Injections were repeated several times and the patient reported subjective improvement of 40% on a visual analogue scale from 0 to 100 [39]. Only the second injection led to mild dysphagia.…”
Section: Dosingmentioning
confidence: 97%
See 2 more Smart Citations
“…Because of the weak effect he did not return to treatment earlier than after 2 years when he received 35 MU of onaBTXA into each sternocleidomastoid muscle and 30 MU onaBTXA into the right longus colli muscle under CT-guidance [39]. Injections were repeated several times and the patient reported subjective improvement of 40% on a visual analogue scale from 0 to 100 [39]. Only the second injection led to mild dysphagia.…”
Section: Dosingmentioning
confidence: 97%
“…Three patients reported weakness of the extensor muscles as a side effect [38]. In a 44-yearold male with severe CACOL, treatment started with 300 MU of aboBTXA in each sternocleidomastoid muscle with little benefit [39]. Because of the weak effect he did not return to treatment earlier than after 2 years when he received 35 MU of onaBTXA into each sternocleidomastoid muscle and 30 MU onaBTXA into the right longus colli muscle under CT-guidance [39].…”
Section: Dosingmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the procedure needs a fluoroscopic EMG-guided approach in an operation room and requires patient sedation. 6,7 The motor improvement achieved by injecting the lower SCM versus the upper SCM could be related to the dynamic progression of anterocollis associated with a chronic increase of intramuscular nerve endings in the distal SCM compared with controls. A recent pathologic study in nondystonic patients reported the presence of 85% of intramuscular nerve ending points located at 20% to 70% of the line from mastoid process to clavicle, and suggested the injection of BoNT in upper SCM at 20% to 40% and lower SCM at 50% to 70% as probable effective points.…”
mentioning
confidence: 97%
“…Herting et al (2004) reported a case of a patient, suffering from severe anterocollis, where repeated computer tomography (CT)-controlled injections of BoNT into the right longus colli muscle allowed a precise location of the needle and injection of the toxin, leading to an obvious improvement of symptoms[85].…”
mentioning
confidence: 99%